Applicability of Gum Karaya in the Preparation and in Vitro Evaluation of Losartan Potassium as Chronotherapeutic Drug Delivery System - Latha, K.; Srikanth, V. V.; Sunil, S. A.; Srinivasa, N. R.; Uhumwangho, M. U.; Shaik, N. B.; Murthy, K. V. R. (Journal of Scientific Research, 2015)
The objective of this investigation is to study the applicability of gum karaya, the natural gum for the preparation and in vitro evaluation of losartan potassium, as Chronotherapeutic Drug Delivery System (ChDDS). The compression-coated timed-release tablets (CCT) containing losartan potassium in the core tablet were prepared by dry coating technique with different ratios of gum karaya as the outer coat. The parameters investigated were tensile strength, friability, in vitro dissolution studies and drug concentration. The optimized formulation was further characterized by powder XRD and FTIR to investigate interactions and no interactions observed. The tensile strength and friability of all the CCT were between 1.06-1.23 MN/m2 and < 0.3% respectively. All the CCT showed a clear lag time before a burst release of drug. However, the lag time of drug release increased as the amount of gum karaya in the outer layer increased. For instance, the lag time of LGK1, LGK2, LGK3, LGK4, LGK5, LGK6 and LGK7 were 16, 10.5, 5.5, 3, 2, 1.5 and 0.5 hrs respectively. The drug content of all the CCT was >98%. Formulation LGK3 was taken as an optimized formulation which can be exploited to achieve ChDDS of losartan potassium for the treatment of hypertension.